(untitled) (University of Khartoum Journal of Agricultural Sciences, 2023)
Twenty-four yearling uncastrated males of Sudan desert sheep(Hamari ecotype), ranging in weight between 26 and 30 kg, were used ina completely randomized design with the objective of studying the effectof feeding different nitrogen levels (14.5%, 16.7% and 18.7% crudeprotein) in complete isocaloric molasses-based fattening diets on sheepperformance, some rumen metabolites (ammonia nitrogen) and blood ureanitrogen. There was no significant treatment effect on average finalweight, average daily gain, daily dry matter intake, daily water intake orfeed conversion ratio. There was a tendency of increased growth rate anddry matter intake with the increase of nitrogen level. The best feedconversion ratio was found at 14.5% crude protein, whereas 16.7% crudeprotein exhibited the least. There was a significant (P<0.05) treatmenteffect on rumen pH when samples were taken before feeding. Treatmenthad no significant effect on ammonia nitrogen or blood urea nitrogenwhen samples were taken before and six hours after feeding. However,treatment failed also to induce a significant (P<0.05) effect on ammonianitrogen three hours after feeding.